The impact of motivation, personal traits of managers and management education on the performances of public healthcare facilities - Karanović, Nevena; Stošić, Sanja (Vojnosanitetski pregled, 2017)
Background/Aim. Exposed to increasing needs of users for better and faster services, more medications and innovative health technologies, managers of healthcare services in the public sector need motivation, permanent updating of information and constant personal development. The aim of this paper was to evaluate, on the basis of experienced healthcare managers, the impact of their motivation, selected character traits, managerial skills and formal education in management on healthcare facilities performances in the public sector. Methods. For the purposes of this study, 97 experienced managers from public hospitals and primary health centers in Serbia answered to 30 questions on the motivation of managers, essential skills for successful management and formal education in management in health facilities. The obtained data about their motivation, governing experience, personal skills and formal education in management were systematized and processed by the Statistical Package for Social Sciences (SPSS). Healthcare facilities performances were expressed by the healthcare facilities ranks in the official annual rankings according to the quality improvement, conducted by the Institute of Public Health of Serbia. Pearson’s or Spearman’s correlation coefficients were used for proving the potential impact of selected factors on performances of healthcare facilities. Results. This study confirmed the association between the healthcare facilities ranks and managers’ abilities to organize the working process (t = -2.453; p = 0.018); expressed high managers’ motivation (ρS = 0.206; p = 0.048) and the length of governing experience (r = -0.198; p = 0.043). Within a 3-year follow-up, this study also confirmed a positive correlation between annual ranks of healthcare facilities and managers quality management courses (ρS = -0.238; p = 0.017) and managers education in human resources management (ρS = -0.234; p = 0.027). Conclusion. In addition to management education, permanent personal development and higher motivation of managers have positive influence on healthcare performances.